ANALISIS DIVERSIFIKASl PRODUK KAYU OLAH.AN PADA INDUSTRI PENGGERGAJIAN TERPADU DI CEPU, JAWA TENGAH - Sylviani Sylviani (Jurnal Penelitian Hasil Hutan, 1991)
Pro4ucta diventfication ia a mutegic tlecmon for integrated fore« indratry a  it will contribute added value either in terms  of  income  1eneriltion or  creation of  employment,  and  to  improve raw materiala. utilization and to  b~n rmrket opportunitin.7b He   the impact of product diversification a dudy  waa conducted at an integrated teak aawmill in Cepu, Central •.liva. TM •average annual UH  of lo1• are 21,896.16   cum oonmting of l 9,!69.46   cum (99'£) f0r •wmDl and•J,117.80   cum• (10%) for verae-r milL TM avmwe  produetioR of  •wn   timber ia 9,681.48   cum per  year ooverift6of the espo~  quality grade  (COS), domedic  quality grade~ and raw materialafor further proce•  with volume• 1,190 •.03  cum (74%); 1,317.80 cum (14"),   and 1,119°.66 cum (12%), re•pectively.The average production of  veneer u 1,394.868   cum per  year cona.ting of the. esport quality lftlde  121.076   cum (9%), domatic quality 180.970  crim (18%), induatrialmaterial 200.189  cum (14%), and dock  892.078  cum (64%). The amaunt of •raw materiai. oonaumedfor ,Parquetteand moulding factories on averageis 8,318.86~   cum ,,.r  year. 7Jle  additional production  oosn  of  other  woodproceaed products  (veneer, ~quette,     moulding) on averafe ia Rp ~186,816,483  per  year with the coefficient variation around 10%. The averageadditional income before ma   generated ia Rp  886,234,808,   per  year, w.ha.t the additional employment  opportunitia  created are 262 or 18,600  rnanday•  or 660,200   manhoura per  year.